SCREENING OF EARLY MATURING RICE VARIETIES/HYBRIDS ARIETIES/HYBRIDS SUITABLE FOR DRY DIRECT SEEDED CONDITION - MAHANTA, SHIVAYOGAYY; K, BASAVARAJ; IBRAHIM, MOHAMMED (The Bioscan, 2016)
An investigation was carried out to evaluate the thirty six early maturing rice varieties/hybrids under Dry Direct Seeded condition during Kharif 2014 at Agriculture Research Station, Gangavathi, University of Agricultural Sciences, Raichur, Karnataka following randomized block design in three replications. Number of tillers per plant at maturity was significantly highest (22.50) in the genotype MT4331 followed by IET 22729 (22.10).Significantly maximum panicle weight (25.43g) was recorded in the genotype RYC 684 followed by US 321 (22.70g).Significantly maximum tillers per square meter (804) was recorded in the genotype IET 22729 followed by MT4331 (729).Out of 36, only two varieties viz, MT4541 (7927 kg/ha) and UPR 2805-14-1-2 (7058 kg/ha) had expressed significantly superior grain yield over check Sahbhagidhan (6258 kg/ha) to an extent of 27 per cent and 13 per cent respectively. The variety 13K 4070 with medium slender grain type had yielded significantly higher grain yield (6970 kg/ha) with 11 per cent increase over Sahbhagidhan and 34 per cent over Local Check (ES-18).The promising genotypes will be further evaluated in multilocation trials under dry direct seeded condition to confirm stability in grain yield and further use as breeding lines.